Il problema dell’existentia e la semantica originaria dell’esse tomistico - Ferraro, Christian (Alpha Omega, 2016)
Summary: A long Scholastic tradition, still very much strong has chosen the term «existence» to translate the famous «esse» of St. Thomas. This choice reveals a decline in the understanding of the original meaning of the thomistic esse which is reduced to being a mere factor that realizes the essence, that is to being a mere function of it. However this choice does not have any grounding in the texts of Aquinas.Key words: Existentia, esse, intensive, act.